2009
DOI: 10.1002/eco.87
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation impacts on near bank flow

Abstract: Vegetation is an important component of stream restoration designs used to control streambank retreat, but vegetation effects on near bank flows need to be quantified. The goal of this research was to evaluate how three-dimensional velocity structure and turbulence characteristics vary with three vegetation treatments: tree, shrub and grass. A second order prototype stream (Tom's Creek in Blacksburg, Virginia, USA) with individual reaches dominated by each vegetation treatment was modelled in a research flume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 49 publications
3
50
0
Order By: Relevance
“…This can be observed for all cases shown in Figure 4, where the streamwise flow velocity at the riverbank does not exhibit a consistent change across the flow depth. This is in accordance to the observations of past studies, reporting non-logarithmic shapes for the streamwise velocity profiles past vegetation patches [11,33].…”
Section: Streamwise Velocitysupporting
confidence: 93%
See 2 more Smart Citations
“…This can be observed for all cases shown in Figure 4, where the streamwise flow velocity at the riverbank does not exhibit a consistent change across the flow depth. This is in accordance to the observations of past studies, reporting non-logarithmic shapes for the streamwise velocity profiles past vegetation patches [11,33].…”
Section: Streamwise Velocitysupporting
confidence: 93%
“…In this study it is found that both bed-shear stress estimates and turbulence intensity results offer consistent trends for the increasing potential of destabilization of the main channel and toe of the riverbank, for high and low vegetation densities respectively. However, as this study has demonstrated, bed-shear stresses cannot be estimated with certainty assuming logarithmic velocity profiles, nor other ways of estimation offer consistent results [11]. This makes it of even greater utility and urgency to identify relevant criteria, which can be used and associated to riverbank stability.…”
Section: Implications For Riverbank Stabilitymentioning
confidence: 82%
See 1 more Smart Citation
“…As noted by Paul et al (), vegetation also affects flow patterns by adding roughness and hence reducing the velocity in vegetated areas, introducing turbulence and inducing scour along the vegetation–channel interface, and forcing flow back towards the open channel (Bertram, ; McBride et al , ; White and Nepf, ). Vegetation can also have a protective role, reducing bank erosion in rivers, estuaries, lakes and coastal zones through deflection of flow away from banks (White and Nepf, ; Hopkinson and Wynn, ), dissipation of wave energy (Möller et al , ), and reinforcement of the soil matrix by plant roots (Pollen and Simon, ; Thomas and Pollen‐Bankhead, ).…”
Section: Quantifying Driving and Resisting Forces Acting On Vegetatiomentioning
confidence: 99%
“…Hession et al, 2003) and channel processes (e.g. Abernethy, and Rutherfurd, 1998;Darby, 1999;Hopkinson and Wynn, 2009). Therefore, any change or trend in vegetation over time can have an effect on response to flood events.…”
Section: Trendsmentioning
confidence: 99%